A NETWORK CREATION OF QUALITY OF LIFE DEVELOPMENT ACCORDING TO THE 5 PRECEPTS OF THE PEOPLE PHON MUEANG SUBDISTRICT AT SAMAT DISTRICT ROI-ET PROVINCE - Khantitalo, Phramaha Khanngoen; Khampheerapanyo, Phra Wiman; Phra Kru Wapeechanthakhun, Phra Kru Wapeechanthakhun (Journal of Graduate MCU KhonKaen Campus, 2020)
This study aimed to 1) investigatea network construction of the 5 Precepts according to Buddhism path 2) examine conditions of problems in following the 5 Precepts to develop the quality of life of the people in Phon Muang Subdistrict, At Samat, Roi Et and 3) analyze patterns of the network creation of life quality development according to the 5 Precepts of the people in Phon Muang Subdistrict, At Samat, Roi Et. This qualitative study was conducted by documentary research method and an in-depth interview 4 groups nemly a groups of monks from Phon Muang Subdistrict. groups of Monks in the Area of Phon Muang Subdistrict. Kamnun groups and The Villege headman group in Phon Muang Subdistrict. and groups of People Phon Muang Subdistrict all total 80 figure/person. The research results were as follows: The 5 Precepts. Is a network that creation guaruntees. the guality of life social security and constitution of life part the Constitution of a network for development of theguality of life. In accordance with the5 Precepts of The People of Phon Mueang Subdistrict. Is the network Is in line with The Social context. By have Lifting The 5 Precepts to development the guality of Life. and dringInto a network with external Social organications.